Two Croatian Reinscriptions of Hamlet - Gjurgjan, Ljiljana Ina (2009)
This paper focuses on two reinscriptions of Hamlet in the second half of the 20th century – Brešan's The Performance of 'Hamlet' (1965) and Paljetak's After 'Hamlet' (1993). These two reinscriptions differ from the previous reception of Hamlet in Croatian culture since the stress is not so much on Hamlet's fate and his psychological anxieties, but on Hamlet as an arche-text. The paper argues that Hamlet as a revenge tragedy ending with catharsis answers man's universal need for order and justice. However, these two reinscriptions of Hamlet subvert this ideological subtext. This archetypal function points to ethical crises brought about by the lack of collective moral values. Brešan's re-writing of Hamlet, the performance of which is staged in a backward Yugoslav village can be described as carnivalesque (the tragedy is re-written as a burlesque). Yet, while the play ends with Hamlet's destiny being silenced – his truth having no relevance because nobody listens while the Kolo sings in celebration of carnal pleasures – it nonetheless expresses a nostalgia for a time in which tragedy (therefore catharsis) was possible and Hamlet could revenge his father. In this respect it is similar to Paljetak's After Hamlet. Though a different sort of play, one that uses Hamlet in a postmodernist way in the sense that it treats it as 'already written' (Hutcheon), Paljetak's play is also nostalgic for a world in which justice is carried out. Written during the siege of Dubrovnik, this play, without referring to this event, is a critique of postmodernity. Blocked by its philosophical approach to the truth as something multi faceted, postmodern Europe is perceived as being ineffectual in its political decisions and unable to act. The world it portrays, (it is set one generation after Hamlet) is therefore unheroic, populated with characters who lack any sense of purpose or moral responsibility.
Projekt MZOS
ENG